Partnerships supporting policies: A social marketing case study of mask supply solutions in South Korea during the COVID-19 pandemic - Paek, Hye-Jin; Hove, Thomas (Frontiers in Public Health, 2023)
Background: South Korea was one of the first countries to experience a large outbreak of COVID-19. Early on, public health authorities recommended mask wearing as one of the main preventive measures against the virus. Compared to people in other countries, most South Koreans were willing to follow this recommendation. However, during the early stages of the pandemic, panic buying and vendor hoarding led to a nationwide mask shortage. The problem was not changing the public’s behavior but rather making masks more available to them. Case Description: To stabilize mask supply and demand, the South Korean government implemented a distribution system that limited mask purchases to two per person per week, in a five-day rotation determined by birth year. The places designated for selling masks included pharmacies, post offices, and marts that had access to data about who had and had not bought their allotted masks. Despite this system, supply problems persisted. In different regions of the country, population density and demand varied, and some pharmacies sold out their stocks of masks earlier than others. Recognizing that people needed a more effective system for finding masks, the government made mask inventory data available to companies and the general public. Three weeks later, about 200 mask apps and web services had been launched. Supplies of masks quickly stabilized, and people could more easily find and buy them. In addition, pharmacies were able to sell out their stocks of masks more efficiently. Conclusion: The South Korean case of mask use during COVID-19 illustrates how all six of the social marketing components (policy, supplemented by products, price, place, promotion, and partnerships) need to be coordinated for effective mitigation of infectious disease. In particular, this case highlights the importance of public-private partnerships among the government, production companies, retailers, and members of the general public.